PROTOTYPING AND SMART TRASH CAN IN THE 5TH GRADE OF ELEMENTARY SCHOOL: A CONNECTION BETWEEN TECHNOLOGICAL PRACTICE AND ENVIRONMENTAL EDUCATION IN FULL-TIME EDUCATION - Alves, Rodrigo Henrique Risso Aires; Pereira, Mariana Arinana Canuto; Araújo, Estephanie Guimarães; Martins, Wilson Ramos; da Silva, Diana Lima; dos Santos, Miquele Araújo; Oliveira, Ludimila Souza; Ponce, Ana Paula Silva (Seven Editora, 2026)
Waste management in the school environment is frequently approached in a merely theoretical manner within teaching schedules. This study analyzed the development of an automated (Smart) trash can prototype, based on the Arduino platform, aiming to integrate ecological awareness with digital experimentation. The qualitative action research was conducted at the Centro Integrado de Atividades Complementares (CIAC), in Humaitá, Amazonas, as part of the "Science Workshop" with 5th-grade Elementary School students. The application of maker culture and electronic prototyping allowed students to diagnose waste production in their classrooms and propose automated solutions. The construction of the artifact fostered critical thinking regarding sustainability and school hygiene, demonstrating that the symbiosis between environmental education and technological practice enhanced the full-time curriculum and promoted investigative protagonism from the early grades.